Fertility Status of Acid Soils under Different Land Use Types in Wolaita Zone, Southern Ethiopia - Mesfin Kassa Cholbe; Fassil Kebede Yeme; Wassie Haile Woldeyohannes (Applied and Environmental Soil Science)
Information on soil fertility status of acid soil of a particular area as affected by land use type is important for developing sound soil management systems for improved and sustainable agricultural productivity. The main objective of this study was to assess the fertility status and effect of land use change on soil physicochemical properties. In this study, adjacent three land use types, namely, enset-coffee, crop, and grazing land use were considered in four districts (i.e., Bolos Sore, Damot Gale, Damot Sore, and Sodo Zuria) of Wolaita Zone, southern Ethiopia. Soil samples were collected from a depth of 0–20 cm from each land use type of the respective districts for physicochemical analyses. The results showed that land use types significantly affected (P≤0.05) soil properties such as bulk density, available P, exchangeable potassium, exchangeable acidity, exchangeable bases (Na, K, Ca, Mg), exchangeable acidity, and CEC. Besides, soil pH, OC, and TN were influenced significantly (P≤0.05) both by districts and land use types. The very strongly acidic soils were found predominantly in the crop and grazing lands whereas a neutral acidity level was found in the enset-coffee land use type of four districts. In conclusion, the study proves that land use type change within the same geographic setting can affect the severity of soil acidity due to over cultivation and rapid organic matter decomposition. Finally, the study recommends an in-depth study and analysis on the root causes in aggravating soil acidity under crop and grazing land use types.